-s-4+6s+4=5

Simple and best practice solution for -s-4+6s+4=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -s-4+6s+4=5 equation:


Simplifying
-1s + -4 + 6s + 4 = 5

Reorder the terms:
-4 + 4 + -1s + 6s = 5

Combine like terms: -4 + 4 = 0
0 + -1s + 6s = 5
-1s + 6s = 5

Combine like terms: -1s + 6s = 5s
5s = 5

Solving
5s = 5

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Divide each side by '5'.
s = 1

Simplifying
s = 1

See similar equations:

| n^2-n-584=0 | | 3x=4x-((4*x)*.0285) | | (-2/7)x(-7/9) | | 16(B+4)=64 | | -6(1+3n)=174 | | 13x+17y=3301 | | 2x-8(2-6x)= | | 10-3x=2(5-x) | | 10X-2X=9+3 | | 9/(3.6-2.1) | | 8-2x=-20+5x | | 6y-2=3y+14-x | | 9x-84=9x-60 | | 3(A-6)=0 | | 14-3(6x-7)=2x+10-35 | | 3x=4x-(4x*0.285) | | 20+3x=36-x | | 6-6(x+2)=10+2x | | 60+3x=12-x | | 12x-7=-17 | | 20+3x=12-x | | (3xy^2)/(21x^4yz^-4) | | 3(5+6)-4(4)=2(4)-16+5(a+1) | | x/1-1/x=8/3 | | 23-3*6/9 | | 7x-2=10x-8 | | -12=-144 | | (3a-2)-(3-5a)=1 | | 7/5p-10=30 | | 8x=296 | | -6+x=-8(1-7x)+2 | | (-5x^3+2x^2-x+5)-(-5x^3+3x^2+5x+3)= |

Equations solver categories